La qualificazione giuridica dello Stato di Israele dal punto di vista della libertà religiosa (Stato, Chiese e pluralismo confessionale, 2023)
The legal qualification of the State of Israel from the point of view of religious freedomABSTRACT. The essay aims to analyze the crucial issue of the State of Israel's relationship with religion, the origin of a 'hybrid' model that is difficult to classify according to classical schemes of ecclesiasticist doctrine. While on the one hand, the millet system still in place in the country guarantees the pluralism of religious communities, which enjoy full normative and jurisdictional autonomy in matters pertaining to family law; on the other hand, the incorporation of Jewish law (halachah) - which exclusively regulates the institutions of Jewish marriage and divorce - among the sources of Israel's legal system makes it a confessional country. Currently, in the absence of a 'secular' discipline, only religious marriage remains recognized in the Jewish State. In recent decades, this has led to the mobilization of increasingly sectors of civil society in support of alternative forms of marriage such as civil unions.SOMMARIO - 1. Confessionale, laico o pluralista? La difficile classificazione di un modello sui generis - 2. Tra conflitto sociale e accomodamento politico - 3. Dal pluralismo religioso al pluralismo istituzionale. La questione del matrimonio civile.